2019
DOI: 10.1177/1474515119879050
|View full text |Cite
|
Sign up to set email alerts
|

Cardiologists’ and patients’ views about the informed consent process and their understanding of the anticipated treatment benefits of coronary angioplasty: A survey study

Abstract: Background: Percutaneous Coronary Intervention (PCI) is a common revascularisation technique. Serious complications are uncommon, but death is one of them. Seeking informed consent in advance of PCI is mandatory. Research shows that PCI patients have inaccurate perceptions of risks, benefits, and alternative treatments. Aim: To assess cardiologists' and patients' views about the informed consent process and anticipated treatment benefits. Methods: Two cross-sectional, anonymous surveys were distributed in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Previous research demonstrates potential improvements in patient education based on "demand-matched" education, that is, the individualization of content, the use of combined media, and more patient-centered information [1][2][3]. Although the importance of adequate patient education is known and several methods to improve education have been explored, the current approach remains insufficient to fulfill the expectations and demands of patients and cardiologists [4]. Whereas a mere 16% of patients were able to explain the benefits of a procedure after a standard care preprocedural consultation, 40% could do so after watching an informative video [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrates potential improvements in patient education based on "demand-matched" education, that is, the individualization of content, the use of combined media, and more patient-centered information [1][2][3]. Although the importance of adequate patient education is known and several methods to improve education have been explored, the current approach remains insufficient to fulfill the expectations and demands of patients and cardiologists [4]. Whereas a mere 16% of patients were able to explain the benefits of a procedure after a standard care preprocedural consultation, 40% could do so after watching an informative video [5].…”
Section: Introductionmentioning
confidence: 99%
“…Web-based study information and informed consent may have an advantage compared to standard person-to-person meetings, as it offers the presumptive participant more time to digest, reflect, and fully understand both the study interventions and the informed consent. For example, a recent study found that patients often misunderstand the meaning of informed consent as it pertains to person-to-person appointments [13]. However, we did not compare comprehension between reading information and informed consent online and at a person-to-person meeting.…”
Section: Xsl • Fomentioning
confidence: 91%
“…2 With regard to informed consent we need to have the skills of decision support, communication and patient engagement such as ‘teach back’ to ensure angioplasty patients receive health information ahead of their treatment in a format that supports recall and comprehension. 3 Patient engagement can be an essential component for developing exercise adherence that can be delivered through internet-based synchronized face-to-face video. 5 Policy-makers should safeguard healthcare system factors that are protective for patient outcomes.…”
Section: Implications For Practice From All Highlighted Articlesmentioning
confidence: 99%
“…With regard to informed consent we need to have the skills of decision support, communication and patient engagement such as ‘teach back’ to ensure angioplasty patients receive health information ahead of their treatment in a format that supports recall and comprehension. 3…”
Section: Implications For Practice From All Highlighted Articlesmentioning
confidence: 99%
See 1 more Smart Citation